PENGUKURAN TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS PELAYANAN ETHIKOPIA COFFEE DI KABUPATEN SLEMAN - Tri Wisudawati; Wahyu Adhi Saputro (JURNAL REKAYASA SISTEM INDUSTRI, 2020)
The coffe shop is not just a place to drink coffe but is a lifestyle. Coffee had a positive development trend in accordance with the habits of many people to drink coffee. One of the cafes that is currently popular in Sleman Regency is Ethikopia Coffee. Ethikopia Coffe visitors are satisfied to enjoy coffe products. This study aims to determine the final level of and italic statisfaction using servqual and in terms of five aspects namely tangibility, reliability, responsiveness, assurance and empathy. This study used 30 samples with method a accidental sampling. Servqual score shows the average value gab for each dimension, tangible (-0.75), reliability (-0.47), responsive (-0.20) assurance (-1.01) and empathy (-0,42). The IPA analysis on Ethikopia Coffe that needs to be improved is in quadrant I is the tangible, responsive and empathic dimensions.